2021
DOI: 10.1159/000514442
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Vascular Fractal Dimensions and Their Association with Macrovascular Cardiac Disease

Abstract: Introduction As the only part of the human vasculature, retina is available for direct, non-invasive inspection. Retinal vascular fractal dimension (DF) is a method to measure the structure of the retinal vascular tree, with higher non-integer values between 1 and 2 representing a more complex and dense retinal vasculature. Retinal vascular structure has been associated with a variety of systemic diseases and this study examined the association of DF and macrovascular cardiac disease in a case-control design. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…FD can provide information relevant to the complex geometrical structure of the vascular tree and it can be defined as a measure of irregularly shaped objects and fragmental property [23,24]. In the literature, several fractal implementation have been developed.…”
Section: Fractal Dimensionmentioning
confidence: 99%
“…FD can provide information relevant to the complex geometrical structure of the vascular tree and it can be defined as a measure of irregularly shaped objects and fragmental property [23,24]. In the literature, several fractal implementation have been developed.…”
Section: Fractal Dimensionmentioning
confidence: 99%
“…The use of bulbar conjunctival vessel length density, i.e., the length of bulbar conjunctival vessels per unit area [ 6 ], can exclude the effect of vessel diameter. Another way is fractal, an algorithm that reflects structural complexity and irregularities, and fractal dimensions can reflect the complexity and density of blood vessels [ 7 ]. Liu et al [ 8 ] confirmed that the fractal dimension of the bulbar conjunctival vessels is positively correlated with the bulbar conjunctival vessel density obtained by pixel counting.…”
Section: Bulbar Conjunctival Microcirculation Parametersmentioning
confidence: 99%
“…Where denotes the grid cell size (a place-designated neuron) and the number of cells. The technique for determining the box-totaling dimension is computed similarly in information theory (entropy theory) and by employing values of the item, as follows: [28,29]…”
Section: Multi-dimensional Fractal (Mdf)mentioning
confidence: 99%
“…A medicinal picture verification technique is accomplished in the researchers' attempt in [24] related to wavelet reestablishment and fractal dimension analysis. The images are eliminated, and a fractal property is formed as the verification image of the pictures when rendering to the singularity of the fractal dimension of the block data [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%